2024
DOI: 10.2196/50064
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Worsened Mental Health of Health Care Workers in Canada During the COVID-19 Pandemic: Cross-Sectional Survey Study

Ali AbdulHussein,
Zahid Ahmad Butt,
Stanko Dimitrov
et al.

Abstract: Background Health care workers (HCWs) in Canada have endured difficult conditions during the COVID-19 pandemic. Many worked long hours while attending to patients in a contagious environment. This introduced an additional burden that may have contributed to worsened mental health conditions. Objective In this study, we examine the factors associated with worsened mental health conditions of HCWs as compared to before the start of the pandemic. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…This resulted in 10 articles for the current scoping review. While four articles also included men in their studies, 20 , 23 , 26 , 28 only outcomes related to migrant women were considered for the current analysis. The authors categorized the predictors from the 10 studies into four main areas: (1) sociodemographic predictors, (2) social adjustment-related predictors, (3) health-related predictors, and (4) psychological predictors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This resulted in 10 articles for the current scoping review. While four articles also included men in their studies, 20 , 23 , 26 , 28 only outcomes related to migrant women were considered for the current analysis. The authors categorized the predictors from the 10 studies into four main areas: (1) sociodemographic predictors, (2) social adjustment-related predictors, (3) health-related predictors, and (4) psychological predictors.…”
Section: Resultsmentioning
confidence: 99%
“…Research has shown that the implementation of public health efforts that promote the QoL of migrant women can have positive social spillover effects. 19 , 20 Research has shown that low QoL among migrant women can have a negative impact on their quality of life. Mental conditions such as depression, anxiety, and stress, as well as physical health, are now understood to have both positive and negative effects on QoL.…”
Section: Introductionmentioning
confidence: 99%